Analysis of e-WOM and Destination Image on Visit Intention - Witarsyah, Nadiya Aulia; Hasanah, Yulia Nur (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2023)
The global spread of the Coronavirus impacts the Indonesian economy, particularly in the tourism industry, Various kinds of tourist attractions in Indonesia are threatened with closing due to the COVID-19 pandemic, and various sectors - supporting tourism sectors such as hotels, restaurants, and retail entrepreneurs are also affected by this coronavirus. Alamendah Tourism Village is one of the tourist attractions affected by the Covid-19 pandemic. This research aims to analyze the impact of e-WOM and destination image on visit intention for the Alamendah Tourism Village, this research uses quantitative method and descriptive causality research. This research was conducted on 100 respondents who had never visited Alamendah Tourism Village. Data was collected by distributing questionnaires, and the data were processed using SPSS 21. The t-test f-test and coefficient determination are used to test hypotheses. It was discovered that the e-WOM had a significant and strong impact on visiting interest and that the destination image also had a significant and strong impact on visit intention. Furthermore, the e-WOM and destination image have a significant and strong impact of 45,9% on visit intention simultaneously, with the rest being influenced by other variables.